NEW INTENSIVE METHODS OF LONG DISTANCE TRAINING AS ONE OF FORM OF FOREIGN LANGUAGE TEACHING - Stamgalieva, Nazym (European Scientific Journal, ESJ, 2014)
In article are considered the possibilities of using of intensive methods of training at learning of foreign languages by means of technologies of distance learning; tendencies of application of technologies of distance learning, the perspective directions and ways with use of modern information technologies at learning of foreign languages are defined.